Adsorption and Dissociation of H2S on V(110), Pd(111) and Pd overlayer on V(110) Surfaces: A Density Functional Theory Study - Mahyuddin, Muhammad Haris (Surya Octagon Interdisciplinary Journal of Science and Technology, 2015)
An interesting prospective pseudomorphic overlayer on bcc surface material as implemented in Pd pseudomorphic overlayer on V(110) surface has been introduced in the frame work of first-principles calculation. Adsorption and decomposition of H2S molecule were calculated on this overlayer structure. In comparison, we also calculated them on their bare V(110) and Pd(111) surfaces. It was found that Pseudomorphic overlayer surface structure weakened the adsorption energy of H2S, SH, S and H compared to its bare Pd(111) and V(110) surfaces. Furthermore, Pd/V(110) surface was found to have higher activation energy barrier for H2S and SH dissociation than its bare Pd(111) and V(110) do. Pd/V(110) surface is predicted to be a promising catalyst membrane used in gas-shift reactor technology because besides its advantage to absorb hydrogen with very high permeation coefficient, sulfur atom is predicted to be adsorbed in a limited amount.